ENGLISH LANGUAGE TEACHING PROBLEMS IN INDONESIA - Gultom, Effendy (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The problems of English teaching in Indonesia have been by many experts and practitioners in the field. Most people focus on the suitable methods of teaching. Some of the methods that have been used are grammar-translation method, direct method,, structural method, reading method, audio-lingual method, situational method, total physical response method, and communicative approach. As a result,Indonesian government or the department of education keeps on changing the methods of teaching English as a foreign language. It is true that we need to keep up with the progress in teaching methodologies. But there are many other factors that we need to consider when we want to be successful in our English teaching program. First of all, the teaching of English as a foreign language has always been considered very important in Indonesia in order to be able to compete with other countries in terms of science, commerce, and technologies. But in real practice the government does not seem to show seriousness in the matter. Let us look at the curriculum and syllabus. In a way, the content of the English syllabus is very dense. It covers all the language skills and components. But the result of the teaching learning process is still not satisfactory.Whenwe look at the teaching-learning process that has been done in public schools, we can probably say that the unsatisfactory result was caused by some factors. First of all, language teaching is different from other subjects teaching. Language teaching is not just a matter of teaching the knowledge. It is more of teaching the skills. It takes a long time to train someone to become fluent in using the language skills.In reality, the class size is usually big while the allotted time for English subject is very little and the meeting frequency is very low. A Foreign language must be taught intensively in small classes with high frequency of meetings. It is best if it is conducted on the daily basis so that the students can achieve quick results and progresses. When the students can feel the progress, they will be motivated to learn more.Keywords: English, language teaching, problems